Survival criterion for a population subject to selection and mutations; Application to temporally piecewise constant environments. (June 2021) - Costa, Manon; Etchegaray, Christèle; Mirrahimi, Sepideh
Abstract: We study a parabolic Lotka–Volterra type equation that describes the evolution of a population structured by a phenotypic trait, under the effects of mutations and competition for resources modelled by a nonlocal feedback. The limit of small mutations is characterized by a Hamilton–Jacobi equation with constraint that describes the concentration of the population on some traits. This result was already established in Barles and Perthame (2008); Barles et al. (2009); Lorz et al. (2011) in a time-homogeneous environment, when the asymptotic persistence of the population was ensured by assumptions on either the growth rate or the initial data. Here, we relax these assumptions to extend the study to situations where the population may go extinct at the limit. For that purpose, we provide conditions on the initial data for the asymptotic fate of the population. Finally, we show how this study for a time-homogeneous environment allows to consider temporally piecewise constant environments.